Economic feasibility of harvesting in the sector sugar-energy: a case study - Mannarelli Filho, Teucle; Donadon, Frederico Andreis B.; Santos, David Ferreira Lopes (Científica, 2018)
Maintaining a positive investment flow over time to ensure business competitiveness is a challenge in the Brazilian sugar-energy sector, structured on a competitive price and cost basis that limits corporate margins. Notwithstanding, credit market asymmetries and low capital market liquidity constrain financing sources for long-term investments. Thus, new financial strategies are required to enable long-term investments that guarantee the longevity of companies. This study analyzes the economic viability of the outsourcing of harvesters in light of the decision to purchase the equipment, as this is a strategic management decision that involves the agricultural activity in sugarcane crop, with intensive use of machinery. For that purpose, a case study was performed in a mill located in São Paulo State, with data obtained between 2014 and 2016. Data related to equipment expenses were extracted from the mill itself, and market information was used to determine the discount rate. The method of analysis was Discounted Cash Flow, which allowed to analyze results through the Internal Rate of Return (IRR) and the Net Present Value (NPV). The strategy of outsourcing harvesters proved to be the decision that provides greater value to the company, since it does not impact the need for investments, besides allowing the tax deductibility of expenses with the outsourced service. The incremental NPV of the outsourcing decision was R$ 396,000/machine and the incremental IRR was negative, signaling that for any discount rate, the decision to outsource is economically superior to the acquisition of harvesters.